2004
DOI: 10.1212/wnl.62.9.1468
|View full text |Cite
|
Sign up to set email alerts
|

Assessment: Transcranial Doppler ultrasonography: [RETIRED]

Abstract: Abstract-Objective:To review the use of transcranial Doppler ultrasonography (TCD) and transcranial color-coded sonography (TCCS) for diagnosis. Methods: The authors searched the literature for evidence of 1) if TCD provides useful information in specific clinical settings; 2) if using this information improves clinical decision making, as reflected by improved patient outcomes; and 3) if TCD is preferable to other diagnostic tests in these clinical situations. Results: TCD is of established value in the scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
130
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(145 citation statements)
references
References 159 publications
4
130
0
7
Order By: Relevance
“…Because elderly patients are difficult for TCD, there seemed to be selection bias of patients in this study. However, as a method which could quantify right‐to‐left shunt (RLS) directly, c‐TCD has a class IIa recommendation for RLS detection as well as TEE,41 and have been recommended as the first choice for screening PFO 22. When compared with TEE,42 it has been demonstrated that contrast‐TCD is more feasible in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because elderly patients are difficult for TCD, there seemed to be selection bias of patients in this study. However, as a method which could quantify right‐to‐left shunt (RLS) directly, c‐TCD has a class IIa recommendation for RLS detection as well as TEE,41 and have been recommended as the first choice for screening PFO 22. When compared with TEE,42 it has been demonstrated that contrast‐TCD is more feasible in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TCD has been proposed as a safe technique with no reports of technique-related complications and to assess brain perfusion noninvasively. The device is of potential benefit for intermittent or continuous monitoring of brain perfusion in the situations where the direct measurement is not available or its reliability is in question (20,22,24,25). Independent of the type of intracranial pathology, a strong correlation between PI and ICP is demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Many centers, including our department, rely on cerebral angiography for the diagnosis of vasospasm. However, the American Academy of Neurology Expert Committee believes the use of TCD on the basis of the fact that although sensitivity and specificity are quite variable and depend on the vessel of interest, severe spasm can be identified with fairly high reliability [56].Recently perfusion computed tomography, diffusion weighted magnetic resonance imaging, and single photon emission computed tomography (SPECT) in detecting vasospasm is under investigation [57]. However, the effect of microsurgical treatment on incidence of vasospasm is not exactly known.…”
Section: Cerebral Vasospasmmentioning
confidence: 99%